2010
DOI: 10.1002/adma.200903462
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties and Photoconductivity of Stacked‐Graphene Carbon Nanotubes

Abstract: Stacked‐graphene carbon nanotubes (SG‐CNTs) obtained via pyrolysis of columnar superstructures of polycyclic aromatic hydrocarbons are studied by electrical transport measurements and scanning photocurrent microscopy. The charge transport in individual SG‐CNTs (see figure) is found to be dominated by variable range hopping. Their photoconductive properties render the SG‐CNTs of interest for photodetector applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…The observed linear behavior of P is advantageous to adjust the optoelectronic device characteristics and paves the way for its application. Similar linear enhancement of Pwith the optical power density was also observed in other RGO‐based compounds and carbon nanotubes . Photocurrent generation mechanism of our system is explained through the band diagram and presented in Figure D.When the RGO‐ZnTTBPc film is illuminated, excitons are generated via absorbing photons.…”
Section: Resultssupporting
confidence: 78%
“…The observed linear behavior of P is advantageous to adjust the optoelectronic device characteristics and paves the way for its application. Similar linear enhancement of Pwith the optical power density was also observed in other RGO‐based compounds and carbon nanotubes . Photocurrent generation mechanism of our system is explained through the band diagram and presented in Figure D.When the RGO‐ZnTTBPc film is illuminated, excitons are generated via absorbing photons.…”
Section: Resultssupporting
confidence: 78%
“…Khan et al [61] used standard four probe method for electrical transport measurements of these multi-walled carbon nanotubes (MWNTs) over the temperature range of 200-4.2 K. From these results, it is found that the variable range hopping (VRH) is responsible for the transport of carriers over the entire temperature range of 200-4.2 K. For the temperature range (200-100 K), three-dimensional VRH is suggested, while twodimensional VRH is observed for the temperature range (100-4.2 K). Lee et al [62] obtained the stacked-graphene carbon nanotubes (SG-CNTs) via pyrolysis of columnar superstructures of polycyclic aromatic hydrocarbons. These SG-CNTs are studied by electrical transport measurements and scanning photocurrent microscopy.…”
Section: Variable Range Hopping In Carbon Nanotubesmentioning
confidence: 99%
“…The motivation for depositing graphene onto the ITO surface relies on its utilization as an acceptor material in the active layer of bulk heterojunction polymeric solar cells 16–18 or as part of a composite material based on a hole‐trapping conducting polymer used for the anode realization of polymeric solar cells 19. The motivation for interfacing nanostructured carbon materials that possess highly specific and widely variable functions to develop a process that is compatible with a variety of materials and device designs was recently under investigation for potential applications 20. Kern and coworkers 20 reported the electrical transport properties of graphene‐carbon nanotubes, as well as their electrical response under illumination, in order to evaluate their use in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for interfacing nanostructured carbon materials that possess highly specific and widely variable functions to develop a process that is compatible with a variety of materials and device designs was recently under investigation for potential applications 20. Kern and coworkers 20 reported the electrical transport properties of graphene‐carbon nanotubes, as well as their electrical response under illumination, in order to evaluate their use in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%